Respuesta :

Answer:

First and third options are equivalent, second and fourth options are not equivalent.

Step-by-step explanation:

Remember the relation:

[tex]a^n*a^m = a^{n + m}[/tex]

and:

[tex](a^n)^m = a^{n*m}[/tex]

We have the expression:

[tex]7^{1/5}*49^{7/5}[/tex]

We know that 49 = 7*7

Then we can write the above relation as:

[tex]7^{1/5}*49^{7/5} = 7^{1/5}*(7^2)^{7/5}[/tex]

We can use the second relationship from the above ones and write this as:

[tex]7^{1/5}*(7^2)^{7/5} = 7^{1/5}*7^{2*7/5} = 7^{1/5}*7^{14/5}[/tex]

Now we can use the first relationship to get:

[tex]7^{1/5}*7^{14/5} = 7^{1/5 + 14/5} = 7^{15/5} = 7^3 = 343[/tex]

Then:

The first option is equivalent.

The second option is not equivalent

The third option is equivalent.

The fourth option is not equivalent.

ACCESS MORE